Root crops for food security in subSaharan Africa - Hahn, S.K. (1994)
Food production in sub-Saharan Africa has not kept up with population growth and the increasing pressure of population on the land has decreased the resource base and caused the farming environment to become vulnerable to unpredictable climatic changes. Thus, there will be more acute food deficits in the future unless the productivity of food crops, including root crops, is increased by at least 3% per annum. Root crops are capable of efficient production of low cost calories under marginal soil conditions. They are very tolerant of stresses and play important roles in the diversified farming systems in the region. As population pressure on the land increases, the importance of root crops has grown and hence they will play more vital roles in the regions food security. Experiences with root crops in the last two decades have shown that the productivity of root crops can be sustained and has substantially increased in certain countries with sound policy and improved technologies to keep up with population growth in sub-Saharan Africa.